The Ideal Concept towards the Welfare of Non-Livestock Animals in the Principle of Utilization and Utilization in Realizing Legal Certainty in Indonesia - Asmariah Asmariah (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2023)
Indonesia has Law No. 41 of 2014 and Government Regulation No. 95 of 2012 to support animal welfare, but the country is still ranked as